THE LEGAL REGULATION OF DIGITAL CURRENCIES AND ITS IMPACT ON COMMERCIAL ACTIVITIES: A COMPARATIVE STUDY BETWEEN ALGERIA, EGYPT, TUNISIA, AND SAUDI ARABIA - Walid Terki, (International Journal of Innovative Technologies in Social Science, 2025)
This study presents a comparative legal analysis of digital currency regulations and their implications for commercial activities in Algeria, Egypt, Tunisia, and Saudi Arabia. By examining the distinct regulatory approaches adopted by these nations, the research aims to elucidate how legal frameworks influence the integration of digital currencies into commercial sectors such as e-commerce, investment, and financial transactions. Employing a doctrinal legal methodology complemented by comparative analysis, the study scrutinizes pertinent legislation, regulatory policies, and economic data to assess the effectiveness of existing legal structures in balancing innovation, consumer protection, and financial stability. The findings reveal significant disparities in regulatory stances, ranging from outright prohibitions to cautious endorsement, each bearing unique impacts on commercial operations. By synthesizing these diverse experiences, the study offers insights and policy recommendations aimed at guiding legislators and stakeholders in formulating balanced regulatory frameworks that foster economic development while mitigating associated risks.